Evaluasi Implementasi Keamanan Informasi pada Sistem Perpustakaan SMKN 1 Banyumas - Putra, Akbar Andhika; Setiyoko, Sigit; Andriyanto, Sabdo Bagus; Imtiyaz, Azmi; Krisbiantoro, Dwi (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid adoption of digital technologies in educational environments has increased the need for secure information systems, particularly in school libraries. This study aims to evaluate the implementation of information security and data privacy within the library system at SMKN 1 Banyumas. A qualitative approach was used, involving direct observations, semi-structured interviews, and document analysis. The findings reveal that although role-based access control and manual data backups are in place, the system still operates over unencrypted HTTP, lacks two-factor authentication, and has no firewall or intrusion detection system. Furthermore, staff members have not received formal cybersecurity training. The study concludes with recommendations for implementing HTTPS, enhancing user authentication mechanisms, deploying network protection tools, and improving staff cybersecurity awareness. These measures are crucial for improving the security posture of educational digital services.